Long-term prophylaxis in von Willebrand disease. Experience from Sweden (Hematology Meeting Reports, 2009)
Von Willebrand disease (VWD) is the most common inherited bleeding disorder, characterized by insufficient or abnormal von Willebrand factor (VWF), a plasma protein essential for primary haemostasis. Patients with VWD are a heterogenous group with respect to clinical manifestations, but the most common bleeding symptoms are mucosal bleedings such as epistaxis and menohrragia. Overt haemarthrosis has been considered rare, even in severe VWD, but in recent data from Italy and the US the incidence is in the range of 40% in patients with type 3 VWD. Serious or repeated bleeding symptoms cause a significant morbidity in this group of patients and they run the risk of long-term sequelae with respect to joint damage. This paper focuses on long experience of prophylaxis in patients with VWD, involving regular infusions of VWF-containing concentrates.